1970
DOI: 10.3329/jce.v25i0.7236
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Occupational Injury among the Workers of Selected Cement Industries in Bangladesh - A Case Study

Abstract: The paper deals with the identification of occupational injury among workers in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
2
7
0
Order By: Relevance
“…Also other studies concerned with these factors among workers of other types of industries such as Wood and oil industries and found similar findings (Assessment, 2011;Jerie, 2012;Meo et al, 2013, Eyayo, 2014. The safety measure and equipment are important factor for the safety and the protection of the workers in different workplaces the present study found that majority of the worker used protective clothing head protection equipment; hand and feet's protection equipment; on the other hand; about three quarters of the studied group used the respiratory equipment, these findings agreed that reported in Bangladeshi and Egyptian studies and these findings consistent with the legislations of occupational safety applied in these factories (Iqbal et al, 2010, Shafik & El-Mohsen, 2012). …”
Section: Chemical Factorssupporting
confidence: 91%
See 2 more Smart Citations
“…Also other studies concerned with these factors among workers of other types of industries such as Wood and oil industries and found similar findings (Assessment, 2011;Jerie, 2012;Meo et al, 2013, Eyayo, 2014. The safety measure and equipment are important factor for the safety and the protection of the workers in different workplaces the present study found that majority of the worker used protective clothing head protection equipment; hand and feet's protection equipment; on the other hand; about three quarters of the studied group used the respiratory equipment, these findings agreed that reported in Bangladeshi and Egyptian studies and these findings consistent with the legislations of occupational safety applied in these factories (Iqbal et al, 2010, Shafik & El-Mohsen, 2012). …”
Section: Chemical Factorssupporting
confidence: 91%
“…In the Bangladeshi study in 2010, Iqba et al, (Iqbal et al, 2010). reported that Arm and leg injuries were the more frequent followed by hand, head and eye injuries due to falls causing wounds and fractures, furthermore, Iqbal et al proved that majority of these injuries incident as a result of welding, belt conveyer and bucket elevator, on the other hand weight lifting represented the second more frequent agent of injuries and lead to back pain, Spondylolisthesis and strains while person fall represented only 7.8% which is lower than our records (Iqbal et al, 2010), the differences in the ranking of the frequency of incidence of these injuries according to the type might attributed to the geographical variation between both countries, and the differences between factories in addition to the variation in the application of safety measures in both countries. It is worth mentioning, that these injuries affected the production process and economic status through the loss of working hours and cost of compensation if present.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-use of PPE can also be the reason. This is consistent with a study done in Kombolcha (Yessuf et al, 2013) and North Gondar (Tadesse and Kumie, 2007) and inconsistent with a study done in Bangladesh (Iqbal et al, 2010), Afar (Yiha and Kumie, 2010) and Addis Ababa (Kifle et al, 2014) this might be due to use of adequate PPE in this studies.…”
Section: Discussionsupporting
confidence: 79%
“…Worldwide occupational exposure to cement dust and other hazards is the cause for skin allergies, eye irritation and other work related injuries (Sana et al, 2013). Job category, work experience and use of personal protective equipments are the associated factors (Iqbal et al, 2010).…”
Section: Introductionmentioning
confidence: 99%